Legalitas Pembagian Harta Warisan Terhadap Ahli Waris Beda Agama Dalam Dua Ketentuan Hukum Waris Yang Berbeda Di Indonesia - Selanno, Julivia Marsel; Saptenno, Marthinus Johanes; Bakarbessy, Andress Deny (Postgraduate Program in Law, Universitas Pattimura, 2024)
Introduction: The inheritance of different religions is one of the contemporary problems in contemporary Islamic legal thought. As time progresses, cases involving inheritance law from different religions are becoming increasingly common. One of the contributing factors is the heirs' (non-Muslim) disagreement with the distribution of assets which is considered unfair.Purposes of the Research: Analyze the application of law in the implementation of the division of inheritance of different religions and the legal consequences in the implementation of the division of inheritance of different religions.Methods of the Research: The research method used is normative legal research relying on a statutory approach and a conceptual approach. Meanwhile, the sources of legal materials used include primary, secondary and tertiary sources of legal materials collected through literature studies and analyzed juridically.Results of the Research: The results of this research show that the legal consequences of resolving inheritance from different religions in its implementation give rise to different interpretations of Judges in considering the law in rulings, as well as giving rise to legal uncertainty, both in the implementation process and the legal status of heirs of different religions, this is because there is no There are definite legal rules, but the implementation of mandatory wills for non-Muslim heirs of Muslim heirs is a form of love and affection between fellow human beings and is an effort to uphold justice and benefit for non-Muslim relatives because their right to inherit is obstructed.